THE INFLUENCE OF COMPONENT SEMANTICS IN MODAL VERB CONSTRUCTIONS WITH THE MODAL VERBS OF “OBLIGATION” ON THEIR GRAMMATICAL AND STATISTICAL FEATURES (ON THE BASIS OF THE TECHNICAL DISCOURSE TEXTS) - Borisenko, T.; Tsinovaya , M.; Tsapenko , L.; Sirotenko , T. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article presents the study of Modal verb constructions with the modal verbs of “obligation” must, have to+ Inf., be to + Inf. functioning in the scientific and technical discourse texts. The material of the research are three technical text corpora, which belong to engineering fields scientifically and technically unrelated to each other – “Electrical Engineering (Energy Supply and Power Management)”, “Automotive Industry” and “Chemical Engineering” – and compiled on the basis of scientific journals of the United States and Great Britain. This allows to obtain the results that are supposedly of a universal nature and can be applied practically to any field of scientific discourse. The goal is to consider: firstly, which semantic groups of verbs (in different grammatical forms) are attached to a particular modal verb, i.e. the following interrelationship is defined: the semantics of a modal verb – semantics and form of a main verb (the second constituent of the modal construction); secondly, to what extent this interdependence affects the usage frequency of the various semantic groups of the main verbs that make up certain MVCs. The results of the research have demonstrated that in Modal verb constructions of this type functioning in the scientific technical discourse texts the predicative meaning of modal verbs is determinant for the semantic features of main verbs connecting to them (modal verbs). The main verb semantics in its turn influences on their (main verbs) grammatical and statistical characteristics. The modal verb must has the highest frequency of use in scientific texts. It gives imperative which underlines the author’s stability of position and faultlessness of the obtained and presented results. Have to + Inf. MVC is much less frequent and it is a result of the modal component semantics of this construction. Modal verb constructions where the modal verb is be to + Inf. are used by the authors of scientific articles quite rarely, which can be also explained by semantic peculiarities of the verb be to + Inf. In Modal verb constructions with the modal verbs of “obligation” must, have to+ Inf., be to + Inf. the passive voice is more preferable than active voice because in the scientific and technical discourse texts human activity does not manifest evidently since the authors should take second place and be present indirectly through their scientific achievements. __________ References • Dictionary by Merriam-Webster (Learners’ Dictionary). Available at http://learnersdictionary.com/ • Grebneva O. V. The modality of necessity in the legislative acts of European Union: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.20 “Comparative-historical, typological and comparative linguistics” / O. V.Grebneva. – Kazan, 2004. – 20 p. • Longman Dictionary of Contemporary English. Available at https://www.ldoceonline • Longman Essential Activator. Available at https://www.twirpx.com/file/287462/ • 5. Olenchuk O. G. Language tools for the presentation of a problematic modality: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.19 “Theory of language” / G. Olenchuk. – Izhevsk, 2012. – 22 p. • Selezneva N. A. Modal verbs usage for implementation of the scientific text functions. Available at https://www.pglu.ru/upload/iblock/1e4/uch_2008_ii_00019.pdf • Terre D. A. Language expressions with the modal lexemes необходимо, нужно, должен / must, ought to, have to: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.19 “Theory of language” / D. A. Terre. – Tver 2006. – 20 p. • Tsinovaya M. V. The typology of models with the verb must on the structural-semantical level (on the material of the English technical sublanguages) / M. V. Tsinovaya // Odessa: Scientific Bulletin of the International Humanitarian University. Series “Phylology”. – № 14. – 2015. • Vasilieva L. V. The modal verb must and its functional equivalents as a segment of functional semantic field of modality: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.04 “Germanic languages” / L. V. Vasilieva. – M., 1990. – 16 p. • Vdovina M. V. Interaction of categories of modality, time, and form in the English sentences with modal verbs): dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.04 ‘Germanic languages’ / M. V. Vdovina. – S.-Petersburg, 2012. – 22 p. • 5th Edition of Webster’s New World Colleage Dictionary. Available at https://sites.google.com/.../downloadpdfebook978/-pdf-webs... -